Exploring destination image, familiarity, information search behaviour, involvement and travel motivation as influencers of ecotourists’ destination loyalty - Yu, Jing; Kasim, Azilah; Sreenivasan, Jayashree; Dzakiria, Hisham; Ul Haq Magray, Ahsan (Turyzm/Tourism, 2020)
This work aims at exploring the influence of selected factors that have received little attention in the past on ecotourism destination loyalty within the context of a developing country. The factors are destination image, familiarity, information search behaviour, involvement and travel motivation. The research was conducted on ecotourists visiting Malaysia who were approached on site and assisted to complete the survey instrument. The sample size was 813, representing a response rate of 47%. Hypotheses were tested using Structural Equation Model. It was found that while there are no linear relationships between the tested variables and destination loyalty, there are findings from the study that offer some managerial implications towards the industry.